Visually Impaired Usability Requirements for Accessible Mobile Applications: A Checklist for Mobile E-book Applications (Journal of Information and Communication Technology, 2023)
The definition of an e-book is a book in an electronic format, which can be beneficial to all readers, mainly those struggling with print books because of their vision impairments. Nevertheless, the visually impaired cannot access regular e-books because they do not meet their unique needs, and they require a more accessible e-book to reach the same expected advantages as those typically seen. Due to the lack of a clear list of these needs, developers are not aware of the specific requirements of the visually impaired for e-book applications. This paper aimed to analyse the visually impaired usability requirements for usable and accessible e-book applications. Three main activities were conducted: reviewing the literature, conducting an online survey of the visually impaired, and comparing the two results obtained earlier to acquire verified usability requirements. This study reviewed current works on the usability and accessibility of e-books from 2010 to 2022. Besides, this study also conducted reviews on common accessibility needs and standards for mobile applications. A total of 24 usability requirements were identified from the literature and compared with ten results from seven visually impaired respondents using an online survey. With these verified usability requirements, designers and practitioners can use them as a checklist to ensure all needs are considered when designing mobile e-books for the visually impaired.